'Dirty pigs' and the xenotransplantation paradox. Issue 4 (25th October 2021) - Haddow, Gill
Abstract : For almost the last 300 years human beings have sought to use organs from non-human animals to repair or replace their own failing organs. This procedure of intraspecies transplant is called xenotransplantation, and despite the continued attempts by researchers, it is yet to be successful. Experiments in xenotransplantation persist, however, partly based on the perceived biological similarities that exist between humans and non-human animals despite the success of xenotransplantation being hampered by the ability of the human body's immune system to attack and therefore reject foreign material. In this article, I explore the sociocultural reactions to xenotransplantation which demonstrates that it is based on a paradox; although non-human animals and humans are thought to be biologically compatible or similar, many assume and emphasise just how different we are from non-human animals. These two positions of 'same but different' are arguably incompatible. I begin by reviewing social science research that demonstrates, despite some variation, a range of persistent concerns towards xenotransplantation including the consequences for personal identity should a person receive a non-human animal organ. I add to this body of work, findings from a mixed-method study involving focus groups and a representative survey with young adults to show that most people prefer to have their organs replaced by materials from their own body and non-human animals the least. These reactions sit within a broader context of a 'wisdom of repugnance' that is brought into existence when our classifications of what is thought to be natural or not is threatened.